Patient and public involvement in contemporary large intensive care trials: Protocol for a meta‐epidemiological study. Issue 9 (12th August 2021) - Barot, Emily; Kjær, Maj‐Brit Nørregaard; Collet, Marie; Crescioli, Elena; Rasmussen, Bodil Steen; Estrup, Stine; Mortensen, Camilla Bekker; Vesterlund, Gitte Kingo; Sivapalan, Praleene; Anthon, Carl Thomas; Bruun, Camilla Rahbek Lysholm; Poulsen, Lone Musaeus; et al.
Abstract: Background: Patient and public involvement (PPI) in randomized clinical trials (RCTs) has increased in recent years but remains the exception rather than the rule. We aim to assess the frequency and extent of PPI in large, contemporary RCTs conducted in an intensive care setting. Methods and design: We will conduct a meta‐epidemiological study of RCTs conducted in intensive care settings published since 2019 and assess their use of PPI. We will extract trial characteristics and verify the use of PPI with trial authors unless specifically stated in the published paper. The primary outcome will be the proportion of trials that use PPI. Secondary outcomes will explore which groups are consulted, at which stage of the trial process this occurs, and by what means these opinions are collected and implemented. Discussion: This meta‐epidemiological study will provide an important insight into the use of PPI in large, contemporary intensive care trials. We wish to reveal ways in which patient involvement could be incorporated more broadly and purposefully here and help to empower clinicians, researchers and patients to collaborate further on future research processes and goals.